Colonial Structure, Chinese Minority and Racial Violence in Indonesia: A Social Reflection - Herdi Sahrasad (Budapest International Research and Critics University, 2019)
Under the Dutch colonial, the Dutch (white skin) become the political, economic and social elites in the colonial society, while middle class consisted of far east people (Chinese, Arab, India, etc), and bumiputera (indigenous Muslim) people laying in lower layer functioning producer of natural resources or traditional (feodal) elite. Dutch elites (top local officials, such as resident), Chinese elite (officer), and traditional elite (regents) are